By the bootstraps - Martin, Alexa (Berkley Romance, an imprint of Penguin Random House LLC, 2026)
"Fueled by a love of romance novels, Luna Starr was destined for a life with her head in the clouds. Her delusional tendencies serve her well...or at least they used to. When life throws her a curveball, she decides it's time to turn her cowboy fantasies into reality and purchases a tiny farm in Celestial, Texas. After all, don't the best heroines try to outrun grief? Tate Jacobs hates cowboys, which is kind of a problem considering his family happens to own the largest ranch in Celestial. Life might not have gone the way he wanted, but as head football coach at his old high school and the town's best (and only) handyman, he's figured out how to stay busy and keep his head down -- until the new girl in town shows up. Luna's new property is a bad accident waiting to happen unless someone helps her with her DIY home renovations. As Tate and Luna spend more time together fixing up her house, unexpected feelings and undeniable chemistry bubble to the surface. Luna might've moved to Celestial to make her cowboy dreams come true, but somewhere beneath the vast Texas skies, she discovers that love in the real world can be far better than she imagined."-- Page [4] of cover.